Blind-spot vehicle detection and distance sensor using PIC-microcontroller - Hamdan, Zharfan (2007)
This work describes the design of blind spot vehicle detection system. The system consists of PIC 16F873 microcontroller as the controller unit and ultrasonic ranger SRF05 as the sensor. The LCD display is also provided by the system to display the distance of approaching vehicle in the blind spot area. The DC servo motor is used to rotate the side mirror of the vehicle and its position is supposed to change whenever a vehicle is detected in the blind spot area. The system has been successfully tested and it can detect any object in a range of 20cm to 3m.